The Roberts Anxiety Scale for Elderly : development and psychometric evaluation : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Albany, New Zealand - Roberts, Margaret Helen (Massey University, 2010)
Psychological literature has clearly expressed the need for a greater understanding of the phenomenon of anxiety in older adults. In turn, this has contributed to the validity issues surrounding the measurement of anxiety in older adults using self-report psychological measures. As such, the need for a new measure of anxiety specific to older adults has been identified within the literature. This study aimed to address these issues in two closely related studies. Study one used thematic analysis to determine the characteristics of anxiety in a sample of 131 community dwelling older adults. The results supported previous research by indicating that how older adults experienced worry was of greater importance than the topic of worry. Social desirability effects were observed in the reporting of anxiety experiences. Study two developed the content for the Roberts Anxiety Scale for Elderly (RASE) by combining psychological theory with the results from study one. The RASE was administered to 203 community dwelling older adults alongside two existing self-report measures. Confirmatory factor analysis found that a three factor structure of worry, negative affect, and somatic sensations best accounted for observed scores on the RASE. Good internal consistency and convergent validity was found for the RASE. Future research should be directed at evaluating the performance of the RASE in clinical populations of older adults.
Keywords: Anxiety in old age; Anxiety in the elderly; Testing; Psychometric scales; Roberts Anxiety Scale for Elderly